Some Highlights on the December Conference on Lu Xun and Devkota - Devkota, Padma Prasad (Literary Studies, 2016)
From December 6-7, 2013, Devkota-Lu Xun Academy organized a two-day exhibition on “Lu Xun: Life and Works” in Kathmandu. The purpose of the event was apparently to bring peoples of China and Nepal together by seeking political and cultural connectivity in the writings of two literary giants, each of whom was born at a time of cultural and political transition of their respective nation into modernity. However, in reality, it sought to import and to establish Lu Xun (1881-1936) as an extreme leftist icon while identifying another such icon from within the nation itself. I intend to conceptualize some differences and similarities between these two poets mostly on the basis of the proceedings of the December Conference.